Energy-saving and consumption-reducing elemene extraction system - YU YUAN; LIU XINGYUAN; JIAN WEIGUANG; GONG JING (2016)
The invention relates to an extraction system, in particular to an energy-saving and consumption-reducing elemene extraction system, which comprises a vacuum pump, a buffer tank with an adsorption layer and a fractionating device, wherein the buffer tank with the adsorption layer is connected with the fractionating device, and the buffer tank is connected with the vacuum pump through a vacuum pump pipeline at the top end of the buffer tank. The energy-saving and consumption-reducing system provided by the invention is provided with the buffer tank with the adsorption layer, so that crystalline components in raw materials can be prevented from entering the vacuum pump and destroying a vacuum pump body; the adsorption layer can effectively prevent a gas processed by cold water from being pumped into the vacuum pump, and simultaneously can adsorb oil stains; and a cut-off valve arranged on the fractionating device can keep the system stable, prevent volatile substances in the raw materials from entering the buff